Finswimming research - Past, present and future - Laurent, B.; Guillaume, G.; Charlie, B. (1st International Scientific Conference of Aquatic Space Activities, 2008)
Finswimming is as old as swimming. Techniques but also technologies have been changed since our ancestor until these last centuries. The last thirty years have seen the most important changes in the finswimming history for four reasons: teaching swimming has become an obligation at school, the democratization of holidays has generated an interest for aquatic activities like fin swimming, development of industries has created a new market on fins and finally the first competitions has accelerated the optimization of products and specifically the monofins. These changes have been studied and supported by different scientific areas such as biomechanics, hydrodynamics, physiology, and psychology. This review is divided into three sections, the past from 1970 to 1997, the present (last 10 years) and the future, and focused specifically on fins and their uses. The future addresses the work that should be attempted in the next ten years.